Political indoctrination in the U.S. Army from World War II to the Vietnam War - DeRosa, Christopher S. (Studies in war, society, and the military., 2006)
DeRosa draws on the records of the army and the Department of Defense's information offices, the content of the indoctrination materials themselves, and soldiers' recollections in analyzing the political messages the nation conveyed to its army during three decades of conscription. He examines how the program took root as an army institution, how its technique evolved over time, and how it interacted with the larger American political culture. In so doing, he explores the implications of trying to impose a political consensus on the army of a democracy.